The answer would be 32. take your 26 and add 18 then subtract 12. then rework it forward if you don't understand.
Answer:
The given sequence is:
a(2)=1
a(3)=3
a(4)=9
We are to find the average rate of change between n=3 and n=4 for the given function.
Average rate of change =
So the average rate of change for the given function from n = 3 to n = 4 is 6
Step-by-step explanation:
-3y = x...so we sub in -3y for x in the other equation
-x + 7y = 70
-(-3y) + 7y = 70
3y + 7y = 70
10y = 70
y = 70/10
y = 7
so we sub in 7 for y in either of the original equations to find x
-3y = x
-3(7) = x
-21 = x
so ur solution is (-21,7)
Answer:
maybe use helpful, caring, kind, encouraging
Answer:
f(x) is reflected over the x-axis and vertically scaled by a factor of 3
Step-by-step explanation:
If you compare the two functions, you see that ...
g(x) = -3f(x)
Multiplication by -1 effects a reflection over the x-axis. (All y-values are transformed to their opposite.)
Multiplication by 3 is a vertical scaling by a factor of 3.
Taken together, f(x) is reflected over the x-axis and vertically scaled by a factor of 3.